Implementasi Buku Panduan Media Replika Gunung Api Sebagai Sumber Pembelajaran Materi Vulkanisme Terhadap Hasil Belajar di MAN 1 Tegal - Benardi, Andi Irwan; Zakiyah, Neza (IJTIMAIYA: Journal of Social Science and Teaching, 2024)
In teaching and learning activities, there are several educational facilities to support learning activities, one of which is that the use of learning media is still very lacking. This research aims to describe the application and analyze learning outcomes, as well as determine student responses regarding the application of a learning media guidebook based on volcano replicas. This research is quantitative research. The sampling technique used is purposive sampling. The sample for this research is class X IPS 3. The variables of this research are the suitability of learning media, the process of applying media in geography learning, and student learning outcomes. Data collection methods are observation, tests, questionnaires, documentation. In this research, data analysis uses N-gain analysis. Based on the results of N-Gain analysis of 30 students. The majority of students (77%) experienced an increase in the medium category, while a small number of students (6%) experienced an increase in the low category, and a group of students (17%) experienced an increase in the high category. The N-Gain value ranges from 0.286 to 0.833, overall the average student increase is 0.512, indicating a sufficient increase in learning outcomes. Implementation of learning using replica-based media based on learning outcomes obtained an average score of 84.16. while in the class implementing learning activities using the lecture method, the average score was 68.16. So media and media application activities can have an influence on learning outcomes.